Coronary Flow Reserve Predicts Longitudinal Myocardial Deformation Capacity in Heart‐Transplanted Patients. Issue 4 (24th November 2015) - Clemmensen, Tor Skibsted; Løgstrup, Brian Bridal; Eiskjær, Hans; Poulsen, Steen Hvitfeldt
Abstract : Aims: This study aimed to evaluate the role of microvascular dysfunction on left ventricular (LV) longitudinal deformation, filling pressures, and exercise capacity in heart‐transplanted (HTx) patients. Methods and Results: Fifty‐seven HTx patients underwent comprehensive echocardiographic graft function assessment during symptom‐limited, semisupine exercise test with simultaneous right heart catheterization. Coronary flow velocity reserve (CFVR) was measured in the left anterior descending artery using pulsed Doppler echocardiography. We divided patients into two groups based on upper and lower median of CFVR. Twenty‐six healthy subjects served as controls. Compared with healthy controls, HTx patients had reduced CFVR (P < 0.0001), exercise capacity (P < 0.0001), and LV longitudinal deformation capacity (P < 0.0001). HTx patients in the reduced CFVR group (CFVR < 2.73) were more symptomatic (P < 0.0001) and had higher prevalence of coronary cardiac allograft vasculopathy (CAV) (P < 0.0001) than patients in the high CFVR group. Systolic function improved in both HTx groups during exercise. However, LV longitudinal myocardial deformation improved significantly more in the high CFVR group (P < 0.0001). Peak exercise LV global longitudinal strain and CFVR were strongly correlated (r = 0.8, P < 0.0001). A weak correlation was observed between CFVR and invasive cardiac index at peak exercise (r = 0.35, P < 0.01) and CFVR and LV filling measured by E/e′ ratio (r = −0.41, P < 0.01) and pulmonary capillary wedge pressure (r = −0.30, P < 0.05). Conclusion: HTx patients have reduced CFVR, exercise capacity, and LV longitudinal myocardial deformation capacity compared with healthy individuals. HTx patients with reduced CFVR are more symptomatic and have increased prevalence of CAV. Furthermore, reduced CFVR is correlated with reduced LV longitudinal myocardial deformation and exercise capacity.